Singapore : Staff Report for the 2005 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This 2005 Article IV Consultation highlights that Singapore's economy has recovered rapidly since mid-2003, having weathered a series of adverse shocks since the Asian crisis. This turnaround owes much to a favorable external environment, supportive macroeconomic policies, and continued structural reforms. Although growth moderated in 2005, the strength of economic activity has been on the upside. Much of the stronger activity reflects higher-than-expected external demand for pharmaceuticals and oil exploration equipment. With stronger-than-expected economic activity, the fiscal outturn for FY2005/06 is likely to be better than budgeted.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet